A cross-sectional study to assess the level of dental anxiety prevailing in undergraduate dental students in Riyadh Elm University - Umbreen Noor Muhammad; Julie Susan Rajan (Wolters Kluwer Medknow Publications, 2020)
Objective: This study was designed to evaluate dental anxiety (DA) level in undergraduate dental students in Riyadh Elm University and its relation with gender and to assess whether the level of DA changes over the whole course of study. Materials and Methods: In this cross-sectional study, the self-reported Modified DA Scale (MDAS) questionnaire was used. The minimum and maximum scores, scored from MDAS, were 5 and 25, respectively. The level of DA was categorized into less anxious (5-11), moderately anxious (12-18), and severely anxious (≥19). Results: The overall response rate was 86% (158 males and 274 females). The mean MDAS from all the participants was 12.06, with 4% of males and 7% of females being severely anxious and 53% of males and 60% of females being moderately anxious. The females were reported to be more anxious than males (P < 0.05). The level of anxiousness was significantly decreasing (P = 0.000) with each successive year of the study. The most anxious situation of all dental procedures was the injection of local anesthesia, followed by noise generated from dental instruments. Conclusion: Female undergraduate dental students and preclinical students were more anxious when compared with males and students of the clinical years, respectively. There is a need for proper dental health education, exposure to clinics, and counseling therapy from the early years of dental training to reduce the level of anxiety.